Analyzing Growth Opportunity of Port from the Resource-based Perspective The Case of Port of Tanjung Pelepas Malaysia - Subhan, Muhammad; Abdul Ghani, Ahmad Bashawir (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
Capturing growth opportunity has become a major integral activity of any port to sustain growth and competitive advantage. One of the famous strategies in leveraging sustainable growth and competitive advantage is the resource-based theory application into port strategic management, viewing resources of the port (internal and external) and its capabilities as the sources for achieving competitive advantage. In this study, we attempt to identify, exploit, and analyze growth opportunity of a Malaysian port from the perspective of the theory. We analyze the portâs resources in terms of values, uniqueness, inimitability, durability, and substitutability. The result is then compared with its rival ports in the region. This study recognizes that the port has successfully identified and exploited its resources for capturing growth opportunity and competing with other ports in the region. We perceive that the port will sustain its growth and competitive advantage as a major port in the region based on its current performance and rivalry circumstances. This study signifies that the higher the level to which resource-based theory of competitive advantage is applied, the higher and longer the growth and competitive advantage will be achieved by the port.